Acceptability of a brief training programme targeting attention and interpretation biases for threat in youth with a history of maltreatment. Issue 3 (11th November 2019) - Lau, Jennifer Y.F.; Sharma, Narayan Prasad; Bennett, Eleanor; Dhakal, Sandesh; Vaswani, Ayesha; Pandey, Rakesh; Niraula, Shanta; Kumari, Veena
Abstract: Background: Tendencies to attend to threatening cues in the environment and to interpret ambiguous situations with negative/hostile intent maintain and may even precipitate internalizing and externalizing problems in young people with a history of maltreatment. Challenging maladaptive information-processing styles using cognitive bias modification (CBM) training may reduce symptoms. Aims: To investigate the acceptability of CBM training in nine young people attending alternate education provision units in the UK, and 10 young people living in out-of-home care institutions in Nepal with a history of maltreatment. Method: CBM training consisted of five sessions of training over a 2-week period; each training session consisted of one module targeting attention biases and one module targeting interpretation biases for threat. A feedback form administered after training measured acceptability. Pre- and post-intervention measures of internalizing and externalizing symptoms were also taken. Results: Most young people (89%) found the training helpful and 84% found the training materials realistic. There were reductions in many symptom domains, but with individual variation. Although limited by the lack of a control condition, we established generalizability of acceptability across participants from two cultural settings. Conclusions: Replication of these findings in larger feasibility randomized controlled trials with measures of attention and interpretation bias before and after intervention, are needed to assess the potential of CBM in reducing anxiety symptoms and its capacity to engage targeted mechanisms.